2016
DOI: 10.1021/acs.jpcb.6b00365
|View full text |Cite
|
Sign up to set email alerts
|

Reorientational Relaxation of Small Solutes in Viscoelastic Liquids

Abstract: The reorientational relaxation times of some small aromatic solutes are determined with nuclear magnetic resonance spectroscopy and time-resolved fluorescence anisotropy measurements in various solvents that exhibit viscoelasticity in the megahertz region. All the reorientational relaxation times in viscoelastic liquids are shorter than those predicted by the hydrodynamic Stokes-Einstein-Debye (SED) relation using the steady-state shear viscosity. The deviation from the SED relation becomes larger in solvents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A classical, and rather simple, model is the small‐step rotational diffusion model based on the Debye diffusion picture, in which the reorientation proceeds through a sequence of very small jumps. It was later on demonstrated that this picture is more applicable to the motion of macromolecules, but not that much to the water molecules (Bagchi, ; Banerjee & Bagchi, ; Laage, ; Laage & Hynes, ; Yamaguchi, Abe, & Nishiyama, ; Zasetsky, Petelina, Lyashchenko, & Lileev, ; Q. Zhang, Chen, et al, ; Q. Zhang, Wu, et al, ). A second picture is the so‐called “flickering cluster” mechanism (Eisenberg & Kauzmann, ), which assumes the formation of hydrogen bonds in water to be cooperative.…”
Section: Studying Water Reorientation Dynamics Based On the Theoretical Modelingmentioning
confidence: 99%
“…A classical, and rather simple, model is the small‐step rotational diffusion model based on the Debye diffusion picture, in which the reorientation proceeds through a sequence of very small jumps. It was later on demonstrated that this picture is more applicable to the motion of macromolecules, but not that much to the water molecules (Bagchi, ; Banerjee & Bagchi, ; Laage, ; Laage & Hynes, ; Yamaguchi, Abe, & Nishiyama, ; Zasetsky, Petelina, Lyashchenko, & Lileev, ; Q. Zhang, Chen, et al, ; Q. Zhang, Wu, et al, ). A second picture is the so‐called “flickering cluster” mechanism (Eisenberg & Kauzmann, ), which assumes the formation of hydrogen bonds in water to be cooperative.…”
Section: Studying Water Reorientation Dynamics Based On the Theoretical Modelingmentioning
confidence: 99%
“…The Journal of Physical Chemistry B pubs.acs.org/JPCB Article reported in a wide range of alkane solvents, 128−130 as well as rotation times in a few normal alcohols 42,99 and alkanes 42,99 reveal benzene motions that are up to 2-fold faster than predicted by the above correlations. Departures of this magnitude are not surprising and may be attributed to variations in a number of molecular features of the solvent such as size, 50,96,97 free volume, 98 and solute−solvent attractions.…”
Section: Discussionmentioning
confidence: 79%
“…Comparable decreases in τ B are also observed in the series of normal alcohols methanol to 1dodecanol, but not in bulk water or in ethylene glycol. Collectively, these observations suggest that solvent characteristics other than viscosity, for example, the solvent size, 50,96,97 free volume, 98 or viscoelasticity 99 are important in determining the friction on benzene. However, the similar values of τ B in isoviscous alkanes and normal alcohols, as well as the comparable values of both D B and τ B in aprotic solvents of similar viscosity but widely differing polarities (Table 1), suggest that electrostatic interactions with solvent contribute little to the friction on benzene motions.…”
Section: Diffusion Coefficients and Rotational Correlation Timesmentioning
confidence: 97%
“…Here, it is noteworthy that the high-frequency extension of the QCM-D measurement achieved in this work enables the observation of the viscoelastic relaxation of ethylene glycol-no relaxation was found in the frequency range of our conventional QCM-D measurement up to 200 MHz. 3) The results of two room-temperature ionic liquids [emim] [TFSA] and [omim][TFSA] are plotted in Fig. 7.…”
Section: Viscoelastic Relaxation Of Viscous Liquidsmentioning
confidence: 99%
“…Therefore, the measurement of the frequency-dependent complex shear viscosity gives information on the time scale of microscopic dynamics, which might also be related to the dynamic solvent effects on fast molecular motion and chemical reaction. 3,4) Measurement below the kHz frequency regime is possible with commercially available mechanical rheometers, and it is routinely applied to soft materials such as polymer systems, surfactant solutions, and colloidal dispersions. However, the frequency range of mechanical rheometers is limited up to the kHz regime, and the rheometers cannot measure viscoelastic relaxation of low molecular weight liquids far from the glass transition.…”
Section: Introductionmentioning
confidence: 99%